Factors affecting elephant distribution at Garamba National Park and surrounding reserves, Zaire, with a focus on human-elephant conflict - Hillman, Smith; de, Merode; Nicholas, Aaron; Buls, Barbara; Ndey, Jerome (Pachyderm, 1995)
Presents preliminary results from investigations focussed on the background of human-elephant conflict in Garamba National Park and adjacent reserves. Concentrations of both elephant and fires have caused the loss of woody vegetation within the Park thus the animals have started to frequent adjacent areas. Mapping of the vegetation and the animal distribution coupled with radio tracking and interviews with people in adjacent areas and long term staff have provided a significant amount of information. Data suggest that the conflict is minimal, and for the most part crop raiding by elephants is rarely done except when the agricultural land lies in the pathway to seasonal ranges or general population movement.